The Influence of Occupational Safety and Job Satisfaction on the Performance of inDrive Drivers in Surabaya - Yuli Indra Aditia; K. Kustini (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of occupational safety and job satisfaction on the performance of inDrive drivers in Surabaya City. The rapid development of the online transportation industry has created challenges in managing driver performance, particularly due to time pressure from the inDrive application’s timer feature and dissatisfaction with the platform’s operational procedures, including the 13.31% commission deduction policy. A quantitative approach was employed by distributing questionnaires to 90 active inDrive drivers in Surabaya City. The sample size was deemed sufficient for Partial Least Squares Structural Equation Modeling (PLS-SEM), which was employed to examine the relationships among the study variables using SmartPLS software. The findings indicate that occupational safety and job satisfaction both have a positive and significant influence on driver performance, with the model explaining 65.2% of the variance in driver performance (R² = 0.652). These results highlight that maintaining safe working conditions and ensuring satisfaction with the platform’s operational system are essential for improving driver performance, particularly in providing timely and reliable services to customers.